Ecotourism Development Strategy of Lhok Batee Jeumpa Reservoir, Bireuen Regency - Ferra Azis,; Halus Satriawan,; Cut Azizah, (Journal of Sylva Indonesiana, 2024)
Bireuen Regency has natural tourism that has the potential to be an ecotourism area, namely the Lhok Batee Reservoir, which is located in Seuneubok Lhong Village, Jeumpa District. This study aims to calculate the carrying capacity of tourist areas, analyze stakeholders based on their influence and importance, and formulate ecotourism development strategies at Lhok Batee Reservoir. The research method uses a survey approach through direct observation in the field with interviews with 50 respondents. The results showed that the carrying capacity of the area was 1,008 people per day. The analysis shows that two classifications of stakeholders play a role in the management of the area and the development of reservoir ecotourism, namely bystanders (Marine Fisheries Food Service; Public Works and Spatial Planning Service; Youth, Sports, and Tourism Service; Environmental Observation Group) and players (Village Government; Regional Development Planning Agency; Environment and Forestry Service). The results of the study formulated an ecotourism development strategy at Lhok Batee Reservoir to increase natural resource conservation efforts, develop the potential of natural resources owned by Lhok Batee Reservoir, develop ecotourism activities while maintaining biodiversity, involve the community to play an active role in tourism activities at Lhok Batee Reservoir, and optimize cooperation programs with stakeholders in marketing Lhok Batee Reservoir ecotourism and in providing environmental training